A Facile Controlled-Synthesis Method of Nanoparticles of Nickel Oxide/Hydroxide Anchored in Graphite/RGO for Alcohol Oxidation. (25th January 2021) - de Oliveira, João P. J.; de Sá, Acelino C.; Sousa, Miguel S. P.; Hiranobe, Carlos T.; Paim, Leonardo L.
Abstract : Composites graphite/reduced graphene oxide electrodes modified with nickel oxy-hydroxide nanoparticles electrodeposited onto electrode surface were developed and applied for the oxidation of ethanol and 2-propanol in alkaline medium. Ni(OH)2 nanoparticles was electrosynthesized in two steps by cyclic voltammetry. Firstly, nickel(II) hexacyanoferrate nanoparticles were electrodeposited, and subsequently Ni(OH)2 was performed in 0.50 mol l −1 NaOH solution. This facile controlled-synthesis method for electrosynthesis of Ni(OH)2 nanoparticles has excellent reproducibility in the manufacture of the modified electrodes. The composite electrodes were characterized by cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), field emission gun scanning electron microscopy (FEG-SEM). Electrooxidation of ethanol and propanol were performed in an alkaline medium, and composite electrode modified with Ni(OH)2 nanoparticles promoted the alcohols electrooxidation. The electrodes showed a linear current relationship as a function of the concentration of the alcohols, and the current density obtained by cyclic voltammetry (50 mV s −1 ) for ethanol was 6.6 mA cm −2 and for 2-propanol was 13.1 mA cm −2 in a solution of 0.1 mol l −1 of NaOH.